Ecology and breeding biology of Lanner Falcons in the Eastern Cape Province, South Africa - Stephenson, Alan (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2001)
Lanner Falcons Falco biarmicus are the commonest large falcons in Africa and this study in the coastal area of the Eastern Cape Province, South Africa investigated their ecology from 1984 to 2000. Lanners have recently been categorised as near-threatened and this study was initiated to ascertain if the population was stable. Breeding success of a small population, in different habitat types, was monitored intensively from 1997 to 2000, and the factors that inhibited breeding were investigated. The earliest onset of incubation was 17 July and the latest 16 August, with 2.2 young fledged per breeding pair over the four-year period. Incubation lasted 32 days and young fledged after 42-45 days. All nest sites were on cliffs with a mean height of 114 m, a mean vertical face of 53 m; 45% of the nests were in ravens' nests. The aspect of cliff sites also influenced breeding success. Radio tracking was used to determine home range, habitat use and hunting methods, with prey species identified. Home ranges were between 66 kmÂ² and 249 kmÂ². Preferred prey was domestic chickens, pigeons and small birds during the breeding season. Foraging ranges were smaller in intensively cultivated areas with seed crops. Data obtained from ringing returns showed that no long distance movements occurred in this region, but two juveniles dispersed 152 km and 127 km. Conservation aspects with possible threats to Lanner Falcons such as poisons, electrocutions and direct persecution are discussed with some recommendations made for future research. Evidence from this study indicates that Lanner breeding success is not limited by nest site availability, but by rainfall timing and prey availability. Lanners foraged more in open areas than areas with tall vegetation, and benefited from intensive agriculture. This population appeared to be healthy and in no danger of declining in the near future.
Keywords: Birds -- Breeding; Birds -- South Africa -- Eastern Cape; Birds -- Ecology; Falcons -- South Africa -- Eastern Cape